Comparative analysis of the state of pro- and antioxidant systems in children under the influence of stress factors of radiation and psychogenic origin (Environment & Health, 2020)
Objective: We evaluated the processes of lipid peroxidation and antioxidant protection in children under the influence of stress factors of radiation and psychogenic origin.Materials and methods: The children of school age – residents of radioactive contaminated territories (RCT) and children-forced migrants from the armed conflict zone exposed to stress factors, were examined. The final products of lipid peroxidation (LPO) reacting with thiobarbituric acid (malondialdehyde – MDA), enzymes-antioxidants – catalase, superoxide dismutase, glutathione peroxidase, glutathione transferase were studied by us to determine the signs of oxidative stress.Results and conclusions: In children-residents of RCT and children-displaced from the zone of armed conflict, the imbalance in the LPO system was revealed, an antioxidant protection is morepronounced among children-residents of RCT. An increase in the serum content of end-products of lipid peroxidation reacting with thiobarbituric acid was observed in children-residents of RCT compared with the control; changes in the activity of antioxidant enzymes such as a decrease in the activity of superoxide dismutase, an increase in catalase activity, glutathione peroxidase, glutathione transferase were observed. In children-migrants from the zone of armed conflict, changes in indicators of the intensity of LPO processes and the activity of enzymes in the antioxidant defense system were unidirectional, but were less pronounced.
Keywords: children; radioactive contaminated territories; zone of armed conflict; lipid peroxidation; antioxidant protection